GH, SEMA3E and TLX gene polymorphism and its association with egg quality traits of quail - Ilhan, F (Journal of the Hellenic Veterinary Medical Society, 2024)
This study attempted to determine the relationship between the GH, Sema3E, and TLX genes and egg quality traits using the PCR-RFLP technique in Japanese quail. Three genotypes and two alleles were obtained by cutting the GH gene with the MspI enzyme, the Sema3E gene with the HaeIII enzyme, and the TLX gene with the PstI enzyme. The allele frequency and the frequency of heterozygous genotypes were higher for all genes. There was no statistically significant relationship between egg quality traits and genotypes. However, it was found that the eggs of the animals with the A allele for the GH gene had a higher shape index. Similarly, eggs from animals with the A allele for the Sema3E gene were found to be heavier. In light of previous studies and these results, it is believed that these genes can be used as selection markers for egg quality traits.